Effect of powdered rosemary (Rosmarinus officinalis) essential oil and phenolic compounds on broiler chickens zootechnical parameters - Samouh, Khaoula Filali (2024)
This work aims at exploiting the essential oil (EO) and phenolic compounds (PC) of rosemary (Rosmarinus officinalis) in a formulation containing leaf powder stabilized with chitin (1%, w/w) to improve chicken meat and investigate their effect on qualitatively and quantitatively broiler chickens’ growth performances. To such a purpose, chicks, at 1 day of age, were distributed in pens on ground divided into four batches. The two control batches were fed with conventional feed, but the positive control contained flavomycin (0.5 g/kg) as growth factor. The two treated batches received a conventional feed supplemented with two doses of 20 and 50 g/kg of the developed formulation. Essential oil and phenolic compound contents in powdered leaves were, respectively, 1.20 and 22.86% in ethanolic extract. 1,8-Cineole (46.88%), followed by camphor (19.20%), α-pinene (9.56%), L.α.-terpineol (5.91%) and β-pinene (4.40%) were the main compounds of the used EO. The two batches of treated chicks showed a significant improvement in body weight (281.88 and 283.75 g, respectively), a decrease in feed conversion and a reduction in mortality (8%), when compared to the control batches. In addition, the elaborated formulation induced catalase activity used as an indicator of cellular antioxidant activity modulation.